Radiographic indices for lumbar developmental spinal stenosis. Issue 1 (December 2017) - Cheung, Jason; Ng, Karen; Cheung, Prudence; Samartzis, Dino; Cheung, Kenneth
Abstract Background Patients with developmental spinal stenosis (DSS) are susceptible to developing symptomatic stenosis due to pre-existing narrowed spinal canals. DSS has been previously defined by MRI via the axial anteroposterior (AP) bony spinal canal diameter. However, MRI is hardly a cost-efficient tool for screening patients. X-rays are superior due to its availability and cost, but currently, there is no definition of DSS based on plain radiographs. Thus, the aim of this study is to develop radiographic indices for diagnosing DSS. Methods This was a prospective cohort of 148 subjects consisting of patients undergoing surgery for lumbar spinal stenosis (patient group) and asymptomatic subjects recruited openly from the general population (control group). Ethics approval was obtained from the local institutional review board. All subjects underwent MRI for diagnosing DSS and radiographs for measuring parameters used for creating the indices. All measurements were performed by two independent investigators, blinded to patient details. Intra- and interobserver reliability analyses were conducted, and only parameters with near perfect intraclass correlation underwent receiver operating characteristic (ROC) analysis to determine the cutoff values for diagnosing DSS using radiographs. Results Imaging parameters from a total of 66 subjects from the patient group and 82 asymptomatic subjects in the control group were used for analysis. ROC analysis suggested sagittal vertebral body width to pedicle width ratio (SBW:PW) as having the strongest sensitivity and specificity for diagnosing DSS. Cutoff indices for SBW:PW were level-specific: L1 (2.0), L2 (2.0), L3 (2.2), L4 (2.2), L5 (2.5), and S1 (2.8). Conclusions This is the first study to define DSS on plain radiographs based on comparisons between a clinically relevant patient group and a control group. Individuals with DSS can be identified by a simple radiograph using a screening tool allowing for better cost-saving means for clinical diagnosis or research purposes.